The role of familiarity in illusions of prediction - Huebert, Andrew M., author; Cleary, Anne M., advisor; Seger, Carol A., committee member; Folkestad, James E., committee member (Colorado State University. Libraries, 2020)
Some researchers have argued that the ability to recall (or the recollection of specific details from the past), and the mechanisms involved in doing so, are also used in imagining and predicting future events. However, the ability to recall is only one facet of memory ability. Another is the ability to detect familiarity with stimuli that relate to previously experienced episodes. One might expect that recall is needed to predict future events, as recollection of what occurred in the past might enable prediction of what happens next in a current ongoing episode. However, research on déjà vu has shown a link between familiarity-detection and illusions of prediction and suggests a role of familiarity intensity in these illusions. The purpose of the present study was to examine the role of familiarity-detection more generally in illusory feelings of prediction and to explore possible mechanisms. Increasing cue familiarity led to a systematic increase in prediction confidence despite having little to no effect on prediction accuracy. These results did not differ according to whether the decision was past or future oriented. The results also did not differ according to whether the future oriented prediction was logically possible or irrational in nature.
Keywords: familiarity; memory; recognition; illusions; cognition; prediction